Ecuador genetic mosaic: biological and adaptive variations across Mestizos, Native Amerindians, and Afro-Ecuadorians. Implications for public health and precision medicine - González-Andrade, Fabricio (Frontiers in Genetics, 2025)
IntroductionUnderstanding human biological diversity is fundamental to improving health and addressing inequities, yet most genomic and biomedical studies remain focused on European and Asian populations. Latin American groups—particularly mestizos, Native Amerindians, and Afro-descendants—are underrepresented, limiting the applicability of global findings. Ecuador, with its tri-hybrid ancestry shaped by Amerindian, European, and African lineages, provides a valuable model to explore how genetic, environmental, and sociocultural factors jointly influence adaptation and disease.ObjectiveTo synthesize and critically evaluate evidence on biological and adaptive variation among Ecuadorian populations, emphasizing methodological transparency, representational equity, and implications for public health and precision medicine.MethodsA narrative review of studies published between 2007 and 2024 was conducted using PubMed, Scopus, and Google Scholar. Eligible works reported empirical data on genetics, immunogenetics, pharmacogenomics, adaptive physiology, or epidemiology among Mestizos, Native Amerindians, and Afro-Ecuadorians.ResultsEvidence supports a tri-hybrid ancestry structure: mestizos show predominantly Amerindian autosomal ancestry with European paternal input; Afro-Ecuadorians retain African heritage with notable Amerindian admixture; and Native Amerindians preserve distinctive lineages and HLA profiles. Well-documented adaptations include altitude tolerance in Andean groups, persistence of the sickle cell trait in Afro-Ecuadorians, and variation in vitamin D status and lactase persistence. Pharmacogenomic differences in CYP2D6, DPYD, and TPMT demonstrate clinical relevance but remain based on small, localized samples.ConclusionEcuadorian populations illustrate how genetic diversity intersects with environment and inequity. Strengthening representativeness, ethical engagement, and translation of genomic evidence into policy are essential to advance equitable precision medicine in Latin America.